A unifying concept of coccolithophore sensitivity to changing carbonate chemistry embedded in an ecological framework. (June 2015) - Bach, Lennart Thomas; Riebesell, Ulf; Gutowska, Magdalena A.; Federwisch, Luisa; Schulz, Kai Georg
Highlights: Calcification rates are stimulated by CO2 and HCO3 − and inhibited by H + . This novel substrate–inhibitor concept is tested with experimental data. The concept enables us to reconcile conflicting results among laboratory studies. We illustrate how this physiological concept can be included in ecological theory. We apply the concept to discuss coccolithophore dispersal in the oceans. Abstract: Coccolithophores are a group of unicellular phytoplankton species whose ability to calcify has a profound influence on biogeochemical element cycling. Calcification rates are controlled by a large variety of biotic and abiotic factors. Among these factors, carbonate chemistry has gained considerable attention during the last years as coccolithophores have been identified to be particularly sensitive to ocean acidification. Despite intense research in this area, a general concept harmonizing the numerous and sometimes (seemingly) contradictory responses of coccolithophores to changing carbonate chemistry is still lacking to date. Here, we present the "substrate–inhibitor concept" which describes the dependence of calcification rates on carbonate chemistry speciation. It is based on observations that calcification rate scales positively with bicarbonate (HCO3 − ), the primary substrate for calcification, and carbon dioxide (CO2 ), which can limit cell growth, whereas it is inhibited by protons (H + ). This concept was implemented in a model equation, tested against experimental data, and then applied to understand and reconcile the diverging responses of coccolithophorid calcification rates to ocean acidification obtained in culture experiments. Furthermore, we (i) discuss how other important calcification-influencing factors (e.g. temperature and light) could be implemented in our concept and (ii) embed it in Hutchinson's niche theory, thereby providing a framework for how carbonate chemistry-induced changes in calcification rates could be linked with changing coccolithophore abundance in the oceans. Our results suggest that the projected increase of H + in the near future (next couple of thousand years), paralleled by only a minor increase of inorganic carbon substrate, could impede calcification rates if coccolithophores are unable to fully adapt. However, if calcium carbonate (CaCO3 ) sediment dissolution and terrestrial weathering begin to increase the oceans' HCO3 − and decrease its H + concentrations in the far future (10–100 kyears), coccolithophores could find themselves in carbonate chemistry conditions which may be more favorable for calcification than they were before the Anthropocene.